The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.12688/wellcomeopenres.14932.2
|View full text |Cite
|
Sign up to set email alerts
|

Functional antibodies against Plasmodium falciparum sporozoites are associated with a longer time to qPCR-detected infection among schoolchildren in Burkina Faso

Abstract: Background: Individuals living in malaria-endemic regions develop immunity against severe malaria, but it is unclear whether immunity against pre-erythrocytic stages that blocks initiation of blood-stage infection after parasite inoculation develops following continuous natural exposure. Methods: We cleared schoolchildren living in an area (health district of Saponé, Burkina Faso) with highly endemic seasonal malaria of possible sub-patent infections and examined them weekly for incident infections by nested P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…Several studies have reported Pf -specific IgM responses in malaria-exposed populations and, in some cases, have shown that these responses associate with protection from clinical malaria ( Boudin et al, 1993 ; Dodoo et al, 2008 ; Richards et al, 2010 ; Adu et al, 2016 ; Oyong et al, 2019 ; Barry et al, 2019 ; Boyle et al, 2019 ). For example, the malaria-resistant Fulani in West Africa have a higher breadth and magnitude of Pf -specific IgM compared with the more susceptible Dogon, whereas Pf -specific IgG did not distinguish between the two groups ( Bolad et al, 2005 ; Arama et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported Pf -specific IgM responses in malaria-exposed populations and, in some cases, have shown that these responses associate with protection from clinical malaria ( Boudin et al, 1993 ; Dodoo et al, 2008 ; Richards et al, 2010 ; Adu et al, 2016 ; Oyong et al, 2019 ; Barry et al, 2019 ; Boyle et al, 2019 ). For example, the malaria-resistant Fulani in West Africa have a higher breadth and magnitude of Pf -specific IgM compared with the more susceptible Dogon, whereas Pf -specific IgG did not distinguish between the two groups ( Bolad et al, 2005 ; Arama et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The rapid infection rates in our study argue against the existence of sterile immune protection 31 , 32 . However, the high proportion of individuals with chronic infections who remained asymptomatic indicates that there was substantial clinical immunity in this age-group 33 .…”
Section: Discussionmentioning
confidence: 57%